An Assessment of the Effectiveness of Riverbank Filtration in a Sewage Plant Effluent-Impacted River Using a Full-Scale Horizontal Well - Noh, Jin-Hyung; So, Soo-Hyun; Park, Ji-Won; Kim, Sang-Yeob; Song, Kyung-Guen; Choi, Jaewon; Kim, Gyoo-Bum; Son, Heejong; Kim, Heeyoung; Maeng, Sung-Kyu (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
From 2014 to 2020, a full-scale horizontal well was operated to investigate the performance of full-scale riverbank filtration (RBF) in the Nakdong River in Korea, which is significantly impacted by the effluents from sewage treatment plants. In this study, an individual lateral full-scale horizontal collector well was investigated for the first time in Korea, and its performance was determined based on the turbidity and levels of iron, total nitrogen, dissolved organic matter, and four selected trace organic contaminants (TrOCs) (tebuconazole, hexaconazole, iprobenfos, and isoprothiolane) in the RBF and Nakdong River. The turbidity of the river was high with an average of 10.8 NTU, while that of the riverbank filtrate was 0.5 NTU or less on average. The average dissolved organic carbon (DOC) concentrations were 2.5 mg/L in the river water and 1.4 mg/L in the riverbank filtrate, which indicated a 44% reduction in DOC content during the RBF. Out of the 10 laterals, 8 laterals exhibited similar levels of iron, manganese, total nitrogen, DOC, and total hardness, electrical conductivity, and turbidity. The characteristics of the remaining two laterals were different. Because the groundwater inflow was relatively low (<10%), the laterals were contaminated by agricultural land use before the installation of the RBF. This is the first study to report changes in water quality according to individual laterals in a river affected by wastewater effluents. The filtration unit exhibited more than 90% removal rates for tebuconazole and hexaconazole. However, the removal rate for iprobenfos was approximately 77%, while that for isoprothiolane was 46%. The four selected TrOCs in this study were not detected in the groundwater. We found that some organic micropollutants were effectively removed by the RBF.